Exercise Is Medicine for Underserved and Vulnerable Populations: Factors Influencing Implementation. Issue 2 (31st March 2022) - Vermeesch, Amber L.; Bustamante, Eduardo E.; Coleman, Nailah; Goldsby, TaShauna; Hasson, Rebecca E.; Hooker, Steven P.; Marquez, David X.; Conroy, Molly B.
ABSTRACT: Purpose: Communities of underserved and vulnerable populations (UVP) are particularly at risk for the negative health consequences related to inadequate physical activity. UVP include individuals from the following groups: racial and ethnic minorities, individuals with disability, those from rural and inner-city areas, elderly and pediatric populations, undocumented immigrants and political refugees, the uninsured/underinsured, those with low income, individuals with chronic medical conditions, non-English-speaking populations, and those with limited health literacy. Exercise Is Medicine (EIM ® ), launched in 2007 by the American College of Sports Medicine (ACSM) and the American Medical Association ®, is a population health initiative aimed at assessing and promoting physical activity among all populations in the United States. The rationale for this commentary is to describe challenges in implementing EIM ® in UVP, discuss potential solutions to these challenges, and share lessons learned from a decade of work in this area to maximize the impact of EIM ® in UVP and thereby increase physical activity levels in UVP. Methods: The ACSM Underserved and Community Health Committee developed a series of symposia presented at the ACSM Annual Meetings in 2012, 2014, 2016, and 2018 to address EIM ® in UVP in terms of barriers, opportunities, health policy, dissemination, and implementation. These symposia included both committee members and other national experts in relevant fields of health disparities, health policy, implementation science, and health care delivery. Symposia highlights and relevant updates were collated by a writing group of committee members for this commentary and organized by applying the Socioecological Model (i.e., individual, relationship, community, societal levels). Results: Recommendations regarding best practices for EIM ® dissemination and implementation among UVP are presented for healthcare providers, exercise professionals, and patients. Key findings include the importance of tailoring EIM ® interventions to improve service to UVP and increase their access to EIM ® resources. Conclusion: For EIM ® to achieve its aim of moving the needle on population health by increasing activity, it will need continued focus on EIM ® implementation among UVP communities with the highest rates of chronic disease and the lowest rates of physical activity.